IN-HOSPITAL BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF CARDIO-RENAL OUTCOMES IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (June 2018) - Konstantinou, K.; Tsioufis, K.; Dimitriadis, K.; Mantzouranis, M.; Koumelli, A.; Fragoulis, C.; Kasiakogias, A.; Vogiatzakis, N.; Tousoulis, D.
Abstract : Objective: Data are scarce regarding the possible prognostic role of blood pressure variability (BPV) in the setting of acute coronary syndrome (ACS). The aim of this study is to determine the impact of in-hospital short-term BPV on cardiovascular outcomes and renal function in patients suffering an acute myocardial infarction (AMI). Design and method: A total population of 150 AMI patients (78.7% male; mean age: 63.57 years;68% hypertensives) underwent 24hr ambulatory BP measurement during their hospitalization. Systolic BPV was derived by coefficient of variability (CV). The study population was divided intoa STEMI group (n = 72) and a non-STEMI (n = 78) one. Cardiovascular outcomes included: new onset of ACS, pulmonary edema, hypertensive emergency, life threatening arrhythmias, whereas worsening of renal function (WRF) was defined as a reduction of GFR > or = 25% according to the RIFLE criteria.No deaths or strokes occurred during the study. Results: In the total study population a significant positive association was demonstrated between SBP CV andthe incidence of total cardiovascular outcomes [odds ratio, 1.240; CI, 1.023–1.503 (P = 0.028)]as well asWRF[odds ratio, 1.394; CI, 1.109–1.753 (P = 0.004)]. Results for the STEMI group were similar regarding both cardiovascular outcomes [odds ratio, 1.38; CI, 1.066–1.794 (P = 0.015)]and WRF [odds ratio, 1.666; CI, 1.126–2.465 (P = 0.011)]. However, the non-STEMI group failed to demonstrate any significant associations. Finally, we conducted a multinomial logistic regression model for the STEMI group, where SBP CV showed relative significance as a predictor of cardiovascular outcomes [odds ratio, 1.317; CI, 0.994–1.746 (P = 0.056)], independently of age, gender and history of hypertension, diabetes mellitus or coronary heart disease. Conclusions: In the setting of STEMI, assessment of systolic BPV using systolic BP CV could have a prognostic role of in-hospital cardio-renal outcomes suggesting a clinical need for further individualization of BP regulation in the integrative ACS management.